(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The outbreak of coronavirus, named as COVID19 by World Health Organization (WHO) has stunned all the nations. This has shown that the world is not prepared for such kind of biological threats. Every nation is trying to mitigate the challenges posed by this disease in their capacity but there is no ray of hope to come out from this crisis. Lockdown and social distancing has posed numerous challenges and affecting the various sectors. Unemployment is at its peak within few months since the outbreak of this pandemic. So, this paper has tried to analyzed the economic impact on GDP across the globe with special reference to its effect on India. The sectors on which it has the maximum impact and those on which this pandemic has the least effect is also studied. On the basis of the study undertaken in reviving the economies from the recession of 2007-08 a concrete model has been reframed that can help the nation in overcoming the grim of COVID19. So this study has tried to discuss the economic impact on the nation but also tried to provide the solution from overcoming of this problem that can help the countries to again revive their economies.